Боспорське місто Тірітака у VІ — на початку V ст. до н. е. (за матеріалами розкопок 2007—2010 рр.) - Зінько, В.М. (Археологія, 2012)
Уперше виявлені споруди грецьких колоністів дозволили уточнити дату заснування Тірітаки та етапи ранньої забудови міста. Исследованиями автора в 2007—2010 гг. в центральной части боспорского города Тиритака внесены существенные коррективы относительно процесса основания и развития этой древнегреческой апойкии. Судя по керамическим материалам, вывод колонии в эту часть побережья Боспора Киммерийского состоялся не ранее 565—560 гг. до н. э. На протяжении первого этапа (вторая треть VI в. до н. э.) жизни на поселении колонисты обитали в небольших полуземлянках. В последней трети VI в. до н. э. начинается второй этап застройки (последняя треть VI — первая четверть V вв. до н. э.) — возведение наземных сырцовокаменных построек. Землянки единовременно были засыпаны, и на их месте возведены дома. Эти постройки выстроены вплотную друг к другу и образовывали небольшие кварталы. В планировочном отношении среди них выделяются дома типичной схемы с двухи трехсторонним расположением крытых помещений вокруг двора. Закладываются основные градостроительные оси полиса, которые будут соблюдаться вплоть до ранневизантийского времени. Площадь города на втором этапе составляла не менее 4,0—5,0 га. В застройке города второго этапа выделяется несколько строительных периодов, из которых в последние (конец VI — первая четверть V вв. до н. э.) произошло два пожара. Дома в центральной части города были сожжены в результате боевых действий на рубеже первой—второй четверти V в. до н. э. On the basis of the research in 2007—2010 in the central part of the Bosporan city Tyritake, the author made significant amendments concerning the process of foundation and development of this Ancient Greek apoikia. Judging from ceramics materials, foundation of the colony in this part of the coast of Cimmerian Bosporus took part not earlier then 565—560 BC. During the first stage (a second third of the 6th c. BC) of life at the settlement, the colonists dwelled in small halfdugouts. In the last third of the 6th c. BC the second stage of building starts (the last third of the 6th c. – the first quarter of the 5th c. BC): surface buildings made of mudbricks and stones. Dugouts were backfilled at a time, and houses were erected on their place. These dwellings built close to each other created small blocks. Concerning their planning, peculiar are the houses with typical scheme of two and threesided arrangement of roofed premises around the yard. Main architectural axes of the city were put, which were followed until the Early Byzantine period. The city area made not less than 4,0—5,0 hectares at the second stage. There are several building periods at the second stage of city building, in the last of which (the end of the 6th c. and the first quarter of the 5th c. BC) two conflagrations happened. Houses in the central part of the city were burned after war actions on the edge of the first and the second quarters of the 5th c. BC